Peningkatan Kemampuan Membaca Pemahaman Menggunakan Teknik Scramble pada Siswa Kelas IV SD - Handayani, Metha Marjuma; Harni, Harni; Sukma, Elfia (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The aim of the study was to describe the improvement of reading comprehension skills with scramble techniques for fourth grade students of SD Negeri 37 Sungai Bangek, Padang City. Research subjects were teachers as researchers and fourth grade students as many as 22 people consisting of 16 men and 6 women. The results of the prabaca phase cycle I 47.72% with less criteria then increased to 78.40% with good criteria in cycle II. The results of the research at the stage when reading cycle I 84.19% with good criteria increased to 94.31% with very good criteria in cycle II. The results of the study in the post-reading stage of the first cycle 59.65% with sufficient criteria increased to 78.40% with good criteria in the second cycle. Keyword : understanding reading, scramble techniques, students